Water Decomposition Occurring During Laser Breakdown of Aqueous Solutions Containing Individual Gold, Zirconium, Molybdenum, Iron or Nickel Nanoparticles - Baimler, Ilya V.; Lisitsyn, Andrey B.; Gudkov, Sergey V. (Frontiers in Physics, 2020)
Generation rates of hydrogen peroxide (H2O2), hydroxyl radicals (•OH), molecular hydrogen (H2), and molecular oxygen (O2) forming during the optical breakdown of aqueous colloidal solutions containing Au, Mo, Zr, Fe, and Ni nanoparticles have been studied. It is shown that the processes occurring during the dissociation of water molecules under the influence of laser breakdown plasma and leading to the formation of various chemical products depend on the material of the nanoparticles present in the colloid. It was found that the highest rates of generation of water decomposition products are observed in aqueous colloidal solutions of Fe and Ni nanoparticles. The use of Au nanoparticles leads to the lowest generation rate. In general, the materials from which the nanoparticles are made, depending on the efficiency of the formation of water decomposition products, are arranged as follows: Ni> Fe> Mo> Zr> Au.